2021
DOI: 10.1111/tpj.15398
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional dynamics during de novo shoot organogenesis of Ma bamboo (Dendrocalamus latiflorus Munro): implication of the contributions of the abiotic stress response in this process

Abstract: Summary De novo shoot organogenesis is an important biotechnological tool for fundamental studies in plant. However, it is difficult in most bamboo species, and the genetic control of this highly dynamic and complicated regeneration process remains unclear. In this study, based on an in‐depth analysis at the cellular level, the shoot organogenesis from calli of Ma bamboo (Dendrocalamus latiflorus Munro) was divided into five stages. Subsequently, single‐molecule long‐read isoform sequencing of tissue samples p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…An optimized combination of cytokinins and auxins was selected to improve the shoot differentiation rate. Recently, transcriptome analysis showed that the expression levels of the majority of ABA-related genes were substantially altered during shoot induction in Ma bamboo, and the exogenous application of an optimized ABA concentration improved the shoot regeneration efficiency (Tu et al, 2021). Our results showed that the shoot differentiation frequency was significantly increased with ABA pretreatment in subculture stage.…”
Section: Discussionmentioning
confidence: 53%
“…An optimized combination of cytokinins and auxins was selected to improve the shoot differentiation rate. Recently, transcriptome analysis showed that the expression levels of the majority of ABA-related genes were substantially altered during shoot induction in Ma bamboo, and the exogenous application of an optimized ABA concentration improved the shoot regeneration efficiency (Tu et al, 2021). Our results showed that the shoot differentiation frequency was significantly increased with ABA pretreatment in subculture stage.…”
Section: Discussionmentioning
confidence: 53%
“…Morphogenesis-related processes such as light-controlled seedling morphology, the formation of floral traits, fruit morphology, as well as thermomorphogenesis, where the morphology changes under high temperatures, all have TFs’ involvement ( Sasaki, 2018 ; Shi et al., 2018 ; Han et al., 2019 ; Zhang et al., 2020a ; Chopy et al., 2023 ). TFs also modulate organogenesis such as leaf, shoot and root development, or even nodule development in the symbiotic relationship between legume and rhizobium ( Sluis and Hake, 2015 ; Tu et al., 2021 ; Chakraborty et al., 2022 ; Liu et al., 2022 ). Gene transcriptional regulation, facilitated by TFs, is essential in controlling numerous biological processes in plants, including signal transduction, stress and defense responses, as well as carbohydrate metabolism ( Seo and Choi, 2015 ; Hoang et al., 2017 ; Shahzad et al., 2021 ; Strader et al., 2022 ; Zou and Sun, 2023 ).…”
Section: Overview Of Transcription Factorsmentioning
confidence: 99%
“…Group 14 with a variance of 35% contained 93 biomarker peptides spanning a distance of 0.12 to 0.94, including Cluster_AAA whose distance was 0.79 (Supplementary Table S4). K-means clustering was well adopted by the proteomics community to group gene products of similar profiles, notably in plants such as bamboo (105), nightshade (106), or grape (107), but to our knowledge not in wheat. In developing corn grains, coordinated protein expression associated with different functional categories was revealed by a k-means clustering analysis (108).…”
Section: Official Officialmentioning
confidence: 99%